Debating as an Authority: Tullia d’Aragona’s. Authorial Self-Fashioning and the ‘Tre Corone’ - Granacki, Alyssa M.; Hogan, Dana V. (Itinerari, 2023)
Often celebrated as the first woman to enter the philosophical debate on the ethics of love, the sixteenth-century philosopher, poet, and cortegiana honesta Tullia d’Aragona has attracted renewed attention in the past thirty years. In her Dialogo dell’Infinita d’Amore (1547) d’Aragona appeals to intellectual authorities to promote her own ethics of love and affirms her qualifications to insert a female voice into the male-dominated debate. This article explores the social and literary avenues for her access to a vernacular literary tradition which she then leveraged to self-fashion an intellectual identity that garnered the respect of her contemporaries. This analysis of d’Aragona’s invocation of the tre corone (Dante, Boccaccio, and Petrarch) in her Dialogo sheds light on her means of entering the debate on the ethics of love and establishing herself as an authority within this intellectual milieu.